1988
DOI: 10.1016/s0196-0709(88)80010-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on normal and otosclerotic bone cell cultures: An advance in understanding the pathogenesis of otosclerosis

Abstract: The authors first reviewed the main theories concerning the pathogenesis of otoselerosis and studied the morphologic and functional characteristics of cell cultures derived from normal and otosclerotic bones. Light transmission and scanning electron microscopy did not permit definite identification of the cultured cells as predominantly osteoblasts, nor did these techniques show significant differences between cultured ceils derived from normal and pathologic bone. Functional tests of the cell cultures proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…These hormones have specific receptors in the plasma membranes of bone cells (Lerner and Lundberg, 2002). The binding of CT to its receptors (Lerner and Person, 2008) is inhibited by blockers of β-adrenergic receptors, such as propanolol (Maurizi et al, 1988;Togari et al, 1997). Several papers in the literature have reported that primary cultures of human osteoblast-like cells expressed a CT receptor-like receptor (CLR) (Villa et al, 2006) and as other osteoblastlike cells (UMR-106) possessed CT-and PTH receptors (Yamaguchi et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…These hormones have specific receptors in the plasma membranes of bone cells (Lerner and Lundberg, 2002). The binding of CT to its receptors (Lerner and Person, 2008) is inhibited by blockers of β-adrenergic receptors, such as propanolol (Maurizi et al, 1988;Togari et al, 1997). Several papers in the literature have reported that primary cultures of human osteoblast-like cells expressed a CT receptor-like receptor (CLR) (Villa et al, 2006) and as other osteoblastlike cells (UMR-106) possessed CT-and PTH receptors (Yamaguchi et al, 1987).…”
Section: Discussionmentioning
confidence: 99%